1978
DOI: 10.1104/pp.62.4.558
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Plastid Number

Abstract: Changes in the physiological state of the multiplastidic alga OHstbodiscus luteus result in a shift in chloroplast complement from 33 to 21 plastids. The effect of this induced change in organelle complement on nuclear and chloroplast DNA levels has been analyzed. Data suggest that the absolute amount of chloroplast and nuclear DNA found within a cell remains constant but that the amount of chloroplast DNA per plastid is inversely proportional to the number of chloroplasts to which that DNA must be distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 31 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Fully expanded trifoliolate leaves (from the third to sixth node from the apex on plants 4 Chloroplast Isolation. Protoplasts were suspended in 0.5 M sorbitol, 50 mm Hepes (pH 7.6), 2 mm EDTA, I mM MgCI2, I mM MnCl2, 10 mM NaHCO3, 0.2 mM NaH2PO4, and I mm Na2H2P207 (buffer B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fully expanded trifoliolate leaves (from the third to sixth node from the apex on plants 4 Chloroplast Isolation. Protoplasts were suspended in 0.5 M sorbitol, 50 mm Hepes (pH 7.6), 2 mm EDTA, I mM MgCI2, I mM MnCl2, 10 mM NaHCO3, 0.2 mM NaH2PO4, and I mm Na2H2P207 (buffer B).…”
Section: Methodsmentioning
confidence: 99%
“…The cell number per ml was determined with a hemacytometer and was the average from counts of 12 fields with five 4-,ul volumes being counted per field. The number of chloroplasts per cell was determined according to the procedure of Cattolico (4). Five ,ul of protoplast suspension in photosynthesis buffer containing approximately 1 x 106 cells/ml was used to prepare chloroplasts for counting.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that ct DNA comprises about 5% of total DNA in the primitive alga Olisthodiscus throughout the growth cycle (2), and as much as 11 to 15% in Chlamydomonas (22,26). Although 9% ct DNA has been estimated for tobacco leaves by the density method (23), reassociation kinetics analysis has indicated that tobacco leaves contain 4% ct DNA and roots less than 1% (21).…”
mentioning
confidence: 99%
“…Upon lysis completion, which was monitored by light microscropy, solid CsCl was added and Hoechst 33258 eye-density centrifugation followed. Alternatively, chloroplasts prepared by Protocol I were lysed as described above and the DNA was purified by the phenol extraction technique of Cattolico (9). Occasionally, in this phenol extraction technique, a pronase digestion step was included before centrifugation.…”
mentioning
confidence: 99%